Cloning vectors for expression of cDNA libraries in mammalian cells. - Murphy, A J (1987)
We have constructed a series of compound cloning vectors (lambda ZD vectors), each consisting of phage lambda arms carrying a modified version of the retroviral expression vector pZIP-neoSV (x)1. cDNA, inserted into a cloning site present in the retroviral vector component, is cloned with high efficiency using the lambda system. A cDNA library in plasmids is then released by homologous recombination between the retroviral long terminal repeats. Retroviral transduction is achieved by transient expression of the released library in a cell line containing a packaging mutant of Moloney murine leukemia virus, followed by cocultivation of these producers with recipient cells. Transcription of cDNAs in the recipient cells is driven by the strong long terminal repeat promoter, and the transcripts, even from truncated cDNAs, can be expressed because translational start sites have been provided in all three reading frames (tri-initiator). Sequences conferring a recognizable phenotype can be rescued by cell fusion. The functionality of the tri-initiator and the rescue of a rare cDNA have been successfully tested using model systems.